2016
DOI: 10.1021/acs.chemrestox.6b00022
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Mitigative Capacity of Dietary Zinc on PCB126 Hepatotoxicity and the Contribution of Zinc to Toxicity

Abstract: Hepatic levels of the essential micronutrient, zinc, are diminished by several hepatotoxicants, and the dietary supplementation of zinc has proven protective in those cases. 3,3′,4,4′,5-pentachlorobiphenyl (PCB126), a liver toxicant, alters hepatic nutrient homeostasis, and lowers hepatic zinc levels. The current study was designed to determine the mitigative potential of dietary zinc in the toxicity associated with PCB126 and the role of zinc in that toxicity. Male Sprague Dawley rats were divided into three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…In the last three decades' deficiency of zinc is because of nutritional factors and also because of the states of several diseases which are recognized (10). Zinc protective effect also shows reduced increase in the serum glutamic pyruvic transaminase (SGOT) and serum glutamic oxaloacetic transaminase (SGPT) activity which was apparent after the acetaminophen administration (11) . We also observed that albino rat's pretreatment with zinc sulphate prevents the serum liver enzymes escalation such as AST, alkaline phosphatase, ALT and serum albumin decrease associated to a certain acetaminophen hepatotoxicity (12) .…”
Section: Discussionmentioning
confidence: 99%
“…In the last three decades' deficiency of zinc is because of nutritional factors and also because of the states of several diseases which are recognized (10). Zinc protective effect also shows reduced increase in the serum glutamic pyruvic transaminase (SGOT) and serum glutamic oxaloacetic transaminase (SGPT) activity which was apparent after the acetaminophen administration (11) . We also observed that albino rat's pretreatment with zinc sulphate prevents the serum liver enzymes escalation such as AST, alkaline phosphatase, ALT and serum albumin decrease associated to a certain acetaminophen hepatotoxicity (12) .…”
Section: Discussionmentioning
confidence: 99%
“…In rats, NAC protected against arsenic-induced liver toxicity, and coadministration of zinc potentiated this effect (71). In a separate study, however, zinc was shown to have limited capacity to mitigate or prevent PCB-induced liver toxicity in rats despite known disruptions in zinc metabolism stemming from PCB exposure (72). These data provide tantalizing evidence that interventions during adulthood have the capacity to mitigate the deleterious effects of some MDCs on tissues regulating metabolic homesostasis by targeting the mechanisms and downstream effectors of MDC action.…”
Section: Strategies To Mitigate the Impact Of Environmental Mdcsmentioning
confidence: 99%